Phenotypic spectrum of NRXN1 mono‐ and bi‐allelic deficiency: A systematic review. Issue 1 (7th May 2019) - Castronovo, Paola; Baccarin, Marco; Ricciardello, Arianna; Picinelli, Chiara; Tomaiuolo, Pasquale; Cucinotta, Francesca; Frittoli, Myriam; Lintas, Carla; Sacco, Roberto; Persico, Antonio M.
Abstract : Neurexins are presynaptic cell adhesion molecules critically involved in synaptogenesis and vesicular neurotransmitter release. They are encoded by three genes ( NRXN1‐3 ), each yielding a longer alpha (α) and a shorter beta (β) transcript. Deletions spanning the promoter and the initial exons of the NRXN1 gene, located in chromosome 2p16.3, are associated with a variety of neurodevelopmental, psychiatric, neurological and neuropsychological phenotypes. We have performed a systematic review to define (a) the clinical phenotypes most associated with mono‐allelic exonic NRXN1 deletions, and (b) the phenotypic features of NRXN1 bi‐allelic deficiency due to compound heterozygous deletions/mutations. Clinically, three major conclusions can be drawn: (a) incomplete penetrance and pleiotropy do not allow reliable predictions of clinical outcome following prenatal detection of mono‐allelic exonic NRXN1 deletions. Newborn carriers should undergo periodic neuro‐behavioral observations for the timely detection of warning signs and the prescription of early behavioral intervention; (b) the presence of additional independent genetic risk factors should always be sought, as they may influence prognosis; (c) children with exonic NRXN1 deletions displaying early‐onset, severe psychomotor delay in the context of a Pitt‐Hopkins‐like syndrome 2 phenotype, should undergo DNA sequencing of the spared NRXN1 allele in search for mutations or very small insertions/deletions. Abstract : Phenotypic spectrum of NRXN1 mono‐ and bi‐allelic deficiency: a systematic review.